Case report: Identification of three novel compound heterozygous SGLT2 variants in three Chinese pediatric patients with familial renal glucosuria - Huang, Huimei; Wu, Xiantao; He, Qing; Liang, Xuqin; Ding, Yi; Li, Zhijuan; Ren, Zhanping; Bao, Ying (Frontiers in Pediatrics, 2022)
Familial renal glucosuria (FRG) is a rare genetic condition featured by isolated glucosuria without hyperglycemia or other kidney diseases. It is caused by pathogenic mutations of the SGLT2 gene, which encodes a sodium–glucose cotransporter responsible for reabsorbing the majority of glucose in the early proximal convoluted tubule. Hitherto, quite an array of variants of SGLT2 have been identified in patients of FRG. In this study, we performed whole exome sequencing on three Chinese pediatric patients with FRG and uncovered three compound heterozygous variants of SGLT2: c.1333C>T (p.Q445X) and c.1130-5 C>G; c.1438G>T (p.V480F) and c.346G>A (p.V116M); c.1175C>G (p.S392C) and c.1333C>T (p.Q445X). Among the total of five variants, c.1333C>T (p.Q445X), c.1438G>T (p.V480F) and c.1175C>G (p.S392C) represented novel variants that had not been reported in any genetic databases. All five variants had extremely low allele frequencies and the amino acids loci affected by missense variants were highly conserved in vertebrate species. Bioinformatic tools predicted that all five variants might disrupt the function of SGLT2, which were likely to be causal for FRG in these patients. Our findings expand the variant spectrum of SGLT2 associated with FRG and provide novel insights into mechanism of action of this transporter, which will aid in the development of novel SGLT2 inhibitors for treatment of type 2 diabetes and cardiovascular diseases.